2004
DOI: 10.1111/j.1523-1739.2004.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coastal Lighting on Foraging Behaviorof Beach Mice

Abstract: Introduction of artificial light into wildlife habitat represents a rapidly expanding form of human encroachment, particularly in coastal systems. Light pollution alters the behavior of sea turtles during nesting; therefore, long-wavelength lights-low-pressure sodium vapor and bug lights-that minimize impacts on turtles are required for beach lighting in Florida (U.S.A.). We investigated the effects of these two kinds of lights on the foraging behavior of Santa Rosa beach mice ( Peromyscus polionotus leucoceph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
109
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(119 citation statements)
references
References 18 publications
(18 reference statements)
6
109
0
4
Order By: Relevance
“…Rotics et al [140] found reduced nocturnal activity and increased intraspecific encounters in nocturnal common spiny mice (Acomys cahirinus) kept in a field enclosure with artificial illumination [140]. Similarly, nocturnal Santa Rosa beach mice (Peromyscus polionotus l.) fed less and had less foraging success in heavily lit beach patches [141]. In bat colonies roosting inside lit buildings, dusk emergence was significantly delayed and of longer duration, and juveniles were smaller and lighter [142].…”
Section: (B) Masking Effect Of Moonlightmentioning
confidence: 99%
“…Rotics et al [140] found reduced nocturnal activity and increased intraspecific encounters in nocturnal common spiny mice (Acomys cahirinus) kept in a field enclosure with artificial illumination [140]. Similarly, nocturnal Santa Rosa beach mice (Peromyscus polionotus l.) fed less and had less foraging success in heavily lit beach patches [141]. In bat colonies roosting inside lit buildings, dusk emergence was significantly delayed and of longer duration, and juveniles were smaller and lighter [142].…”
Section: (B) Masking Effect Of Moonlightmentioning
confidence: 99%
“…Conversely, although light increases the detectability of prey, it could be detrimental if prey availability decreases because prey remain closer to cover when it is brighter (Lockard & Owings 1974, Kaufman & Kaufman 1982, Clarke 1983, Wolfe & Tan Summerlin 1989, Kotler et al 1991, Daly et al 1992. With increased illumination, prey move and forage less (Abramsky et al 2004, Bird et al 2004, Rotics et al 2011, likely in response to in creased predation risk (Clarke 1983, Kotler et al 1991, so predators may need to search larger areas to find the same amount of prey under such conditions (Rockhill et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, when it intrudes into the natural dark phase, it may lead to the disruption of circadian organization and desynchronization in timing of the different biological rhythms, which is associated with various health risks and the disturbance of ecological systems (Bird et al, 2004;Navara and Nelson, 2007;Haim and Portnov, 2013). Although the effects of night-time light exposure on circadian organization are widespread, few studies have investigated the effects of varying intensities of daytime lighting on photoentrainment.…”
Section: Discussionmentioning
confidence: 99%